Effect of curcumin, the active constituent of turmeric, on penicillin-induced epileptiform activity in rats - Tamaddonfard, Esmaeal (Mashhad University of Medical Sciences, 2012)
Objective: Curcumin is a major constituent of turmeric and has many biological functions such as anticancer and anti-inflammatory effects. The present study was conducted to investigate the effects of curcumin and diazepam in separate and combined treatments on penicillin-induced seizures in rats. Materials and Methods: In urethane-anesthetized rats, epileptiform activity was induced by intracortical (i.c.) administration of penicillin (200 IU, 1 µl), and frequency and amplitude of spike waves were analyzed using electrocorticographic recordings. Results: Intraperitoneal (i.p.) injections of curcumin at doses of 100 and 200 mg/kg, and intracerebroventricular (i.c.v.) injection of diazepam at a dose of 5 µg significantly (p<0.05) reduced both frequency and amplitude of spike waves. Co-administrations of curcumin (50 mg/kg, i.p.) with diazepam (5 µg, i.c.v) enhanced the antiepileptic effect of diazepam (5 µg, i.c.v). Conclusion: The results suggested that both curcumin and diazepam suppressed penicillin-induced epileptiform activity. A potentiation effect was observed between curcumin and diazepam in reducing penicillin-induced seizures.